2011
DOI: 10.1007/s12298-011-0090-6
|View full text |Cite
|
Sign up to set email alerts
|

Mercury induced phytotoxicity and oxidative stress in wheat (Triticum aestivum L.) plants

Abstract: The phytotoxicity and oxidative damage in response to different concentrations of Hg (0.0, 2.5, 5.0, 10 and 25 μM) were evaluated in wheat plants. The root and shoot growth, content of chlorophyll and total soluble protein declined at 10 and 25 μM Hg. Roots of the plant were more affected as compared to the shoot. The malondialdehyde (MDA) quantity enhanced in the roots of wheat plants treated with 10 and 25 μM Hg and in the leaves of plants treated with 25 μM Hg. The concentration of H 2 O 2 decreased at low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 38 publications
10
32
0
Order By: Relevance
“…SAHU et al (2012) observed that the supply of Hg both at moderate (5µM) and high concentration (25µM) reduced the concentrations of K, Ca and Mg in Triticum aestivum. Reductions of K, Ca and other mineral nutrients under the influence of Hg have been reported in Marrubium vulgare and Rumex induratus (MORENO-JIMENZ et al, 2007).…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…SAHU et al (2012) observed that the supply of Hg both at moderate (5µM) and high concentration (25µM) reduced the concentrations of K, Ca and Mg in Triticum aestivum. Reductions of K, Ca and other mineral nutrients under the influence of Hg have been reported in Marrubium vulgare and Rumex induratus (MORENO-JIMENZ et al, 2007).…”
Section: Resultsmentioning
confidence: 94%
“…In our previous studies (CALGAROTO et al, 2010;CALGAROTO et al, 2011), it was found severe lipid peroxidation of P. glomerata plantlets exposed at the highest level of Hg (50µM) tested. Increase in oxidative stress by reactive oxygen species in response to Hg has been observed in roots and leaves of Medicago sativa (ZHOU et al, 2008), Triticum aestivum (SAHU et al, 2012), Cucumis sativus (CARGNELUTTI et al, 2006), and several other plants. Active oxygen species bring about the peroxidation of membrane lipids (CARGNELUTTI et al, 2006;ZHOU et al, 2008;CALGAROTO et al, 2010), which leads to increased membrane permeability (SAHU et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations